Individualization of society and religionization of individuals: Resacralization in postmodernity (second modernity) - Shimazono, Susumu (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
It is widely perceived that the period called modern times came to a turning point in the latter half of the 20th century. There is no objection to exploring the characteristics of «postmodern» or «second modern» times with the concept of «individualization» as a key as Zygmunt Bauman and Ulrich Beck did. When this is applied to «religion», a conclusion may be extracted that individualization is progressing also in religions, and that the power of religions that functions to integrate followers as a group is retreating. In fact, later developments have not followed to confirm this view. Rather, resacralizationand the rise of public religions have come to be discussed. In this paper, the author will attempt further to explicate how we can consistently understand the tendency of individualization in religions, and the tendency of forming new kinds of religious communality.